2005
DOI: 10.1523/jneurosci.0514-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Overexpressing the Macrophage Colony-Stimulating Factor Receptor Are Neuroprotective in a Microglial-Hippocampal Organotypic Coculture System

Abstract: Microglia with increased expression of the macrophage colony-stimulating factor receptor (M-CSFR; c-fms) are found surrounding plaques in Alzheimer's disease (AD) and in mouse models for AD and after ischemic or traumatic brain injury. Increased expression of M-CSFR causes microglia to adopt an activated state that results in proliferation, release of cytokines, and enhanced phagocytosis. To determine whether M-CSFR-induced microglial activation affects neuronal survival, we assembled a coculture system consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 62 publications
1
52
0
1
Order By: Relevance
“…Interestingly, the absence of M-CSF and microglial proliferation was associated with enhanced neuronal sensitivity to injuries and increased neuronal cell death after cerebral ischemia (Berezovskaya et al, 1996;Fedoroff et al, 1997). Conversely, addition of M-CSF conferred neuroprotection in the microglialhippocampal organotypic coculture system (Vincent et al, 2002;Mitrasinovic et al, 2005). At present, the mechanism of M-CSF neuroprotection remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the absence of M-CSF and microglial proliferation was associated with enhanced neuronal sensitivity to injuries and increased neuronal cell death after cerebral ischemia (Berezovskaya et al, 1996;Fedoroff et al, 1997). Conversely, addition of M-CSF conferred neuroprotection in the microglialhippocampal organotypic coculture system (Vincent et al, 2002;Mitrasinovic et al, 2005). At present, the mechanism of M-CSF neuroprotection remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to overcome this limitation, we chose to use a well established ex vivo model of neuroinflammation (Ullrich et al, 2001;Mitrasinovic et al, 2005;Neumann et al, 2006). Using this model, we were now able to demonstrate that indeed only PMNs sharply increased neuronal damage associated with transient ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the neurotoxic properties of activated microglia after ischemic or excitotoxic damage (Giulian et al, 1993;Kim and Ko, 1998;Rogove and Tsirka, 1998;Yrjanheikki et al, 1999), whereas considerable evidence shows that microglia triggered by injured/dying neurons mediate a reduction of neuronal damage and induction of tissue repair (Morioka et Considering these controversial findings on the role of PMNs and microglia during transient ischemia, strikingly few studies have evaluated the direct effect of these immune cells on neuronal survival/damage (Dinkel et al, 2004;Mitrasinovic et al, 2005). Despite that, although the combined recruitment of both cell types to tissue sites affected by cerebral ischemia is well established, a potential direct interaction of both immune cell types has not been investigated in depth.…”
Section: Introductionmentioning
confidence: 99%
“…29 The result indicates that activated macrophages at the injured site could provide a beneficial microenvironment, which is good for regeneration of sensory axons, possibly due to the release of transforming growth factor-b (TGF-b). 30 Mitrasinovic et al 31 showed…”
Section: Dual Effect Of Macrophages After Scimentioning
confidence: 99%